Introduction: Epigraphy, the Qurʾān, and the religious landscape of Arabia - Grasso, Valentina; Davitashvili, Ana; Abuhussein, Nadja (Millennium, 2023)
A wide range of archaeological finds is rapidly expanding our knowledge of the pre-Islamic cultural milieu and the political structures of the Arabian Peninsula during Late Antiquity, and thereby of the Qurʾān’s cultural context. This material can offer a complementary reading to the literary accounts on pre-Islamic Arabia, which were mostly composed outside of Arabia or long after the late antique period. There is a growing need to make the recent exciting discoveries of scholars working on the Qurʾān and Arabia more widely accessible to historians who may not have a solid background in archaeology and epigraphy. As such, the ERC project “The Qur'an as a Source for Late Antiquity” (QaSLA) organized a conference, titled “Epigraphy, the Qur'an, and the Religious Landscape of Arabia”, which took place in Tübingen on 8 - 10 September 2022. The three-day international conference brought together specialists in epigraphy as well as scholars of the Qurʾān to explore how recent epigraphic and archaeological findings and research have been changing our understanding of the Qurʾān and the Arabian religious, cultural, and political landscape. Accordingly, the conference sought to integrate new archaeological finds with ongoing studies on the genesis of the Qurʾān, its Arabian background, and the broader cultural milieu of pre-Islamic Arabia with a special focus on the dawn of Islam. The conference also featured an important contribution by Peter Webb on pre-Islamic poetry, another neglected corpus of inquiry into the history of pre-Islamic Arabia. Aiming to foster discussion between scholars, each panel was paired with a specialist on the Qurʾān or the wider history of Arabia.
Gesehen am 10.07.2024